PENGGUNAAN MATEMATIKA REALISTIK UNTUK MENINGKATKAN DISPOSISI MATEMATIS SISWA SMP - Vincentia Septi Puspitawati; Georgius Rocki Agasi (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
The problem of mathematics learning often happens in mathematics teaching that seems far from the real problem. Realistic mathematics learning can help students to understand about mathematics concepts that abstract for them. If the teachers use real context in mathematics learning, students will be more attracted and interested. The purpose of this research is to look at the effect of realistic mathematics learning towards student's mathematical disposition. The method of this research is descriptive quantitative. The subjects were 35 students of SMP N 14 Yogyakarta grade 7 and this research held in one month. The instrument is students' mathematical disposition scale questionnaire. The students fill the questionnaire before and after they are given a treatment. The result of the questionnaire was analyzed using descriptive statistics, by looking at the average before and after treatment and categorized according to the average value. Based on the results of the descriptive statistical analysis showed that an average of students’ mathematical disposition has increased. The average value of students in pre-treatment is 96.02 with the medium category and then after treatment is given to the 109.44 with the high category